Reactive microglia and macrophage facilitate the formation of Müller glia-derived retinal progenitors - Fischer, Andy J. (2014)
In retinas where Müller glia have been stimulated to become progenitor cells, reactive microglia are always present. Thus, we investigated how the activation or ablation of microglia/macrophage influences the formation of Müller glia-derived progenitor cells (MGPCs) in the retina in vivo. Intraocular injections of the Interleukin-6 (IL6) stimulated the reactivity of microglia/macrophage, whereas other types of retinal glia appear largely unaffected. In acutely damaged retinas where all of the retinal microglia/macrophage were ablated, the formation of proliferating MGPCs was greatly diminished. With the microglia ablated in damaged retinas, levels of Notch and related genes were unchanged or increased, whereas levels of ascl1a, TNFα, IL1β, complement component 3 (C3) and C3a receptor were significantly reduced. In the absence of retinal damage, the combination of insulin and Fibroblast Growth Factor 2 (FGF2) failed to stimulate the formation of MGPCs when the microglia/macrophage were ablated. In addition, intraocular injections of IL6 and FGF2 stimulated the formation of MGPCs in the absence of retinal damage, and this generation of MGPCs was blocked when the microglia/macrophage were absent. We conclude that the activation of microglia and/or infiltrating macrophage contributes to the formation of proliferating MGPCs, and these effects may be mediated by components of the complement system and inflammatory cytokines.